(untitled) (CIPEEX, 2025)
INTRODUCTION: Brazil ranks second worldwide in the number of plastic surgeries performed, and this rate has been steadily increasing. The scientific and social relevance of this study lies in the attempt to understand the growing demand for plastic surgeries in Brazil. OBJECTIVE: To investigate, based on recent literature, the relationship between undergoing plastic surgery and the enhancement of self-esteem among Brazilian individuals. METHODOLOGY: An integrative literature review was conducted using articles retrieved from SciELO and Google Scholar databases. Using descriptors combined with Boolean operators (AND, OR), 1,345 articles were identified, of which 5 met the inclusion criteria. Exclusion criteria: publications prior to 2019, non-free access, and studies involving non-adult patients. Inclusion criteria: studies involving Brazilian patients of both sexes and texts written in Portuguese. RESULTS: The reviewed studies indicated that surgical procedures increase self-esteem in the postoperative period. Social, familial, and media-related factors were observed to influence the decision to undergo surgery. Gender differences were identified: women seek a younger and more attractive appearance, while men generally undergo procedures later in their careers, aiming to conform to professional standards. CONCLUSION: The relationship between plastic surgery and self-esteem is strongly mediated by sociocultural and media influences. Aesthetic procedures indeed enhance patients’ self-esteem; however, further research is necessary to deepen the understanding of this phenomenon.